Legal Certainty In The Application of Sanctions for Contempt of Court in Criminal Evidence in Indonesia - Fadillah, Yohana Alfine; Mustikasari, Dyah Ayu; Rato, Dominikus; Ohoiwutun, Y. A. Triana (Ranah Research : Journal of Multidisciplinary Research and Development, 2025)
The legal issues related to insults by state officials against judicial institutions highlight two important aspects. First, the application of sanctions for this action raises questions about legal certainty, because it can damage the integrity of the judicial institution and reduce public trust. Second, there are challenges in proving elements of insult that are often subjective, especially when state officials use the right to freedom of speech as a defense. The complex process of proof requires strong evidence, and a balance between protecting the honor of the judiciary. This study discusses the application of criminal evidence related to insults by state officials against judicial institutions in the context of legal certainty. Based on Article 240 of the Criminal Code which regulates insults against state institutions, including the judiciary, this study highlights the uncertainty in the application of sanctions due to the ambiguous definition of insult and the complaint procedure that depends on the party who feels aggrieved. Gustav Radbruch's legal approach to legal certainty is raised to explain the importance of consistency and clarity of law in these cases. Inconsistent law enforcement can lead to injustice, especially when state officials are protected from criticism under the pretext of insult, which ultimately undermines public trust in the judicial system.